O Todo e as Partes: Subsídios para a leitura do ensaio Amor Evolucionário de Charles Sanders Peirce - Antônio, Basílio João Sá Ramalho (2006)
In this dissertation, we have sought to provide a Portuguese version for Peirce s 1893 essay Evolutionary Love , as well as to offer theoretical subsidies for its reading. With this aim, we developed, in the first chapter, the analysis of the modus operandi of the law of mind, for Peirce has made it the great law through which all regularities of the universe were formed. Thus, we went through the concept of continuity, which is the condition of possibility for understanding the dynamics of the mental law of association of ideas. The association of ideas, which structures the formation of all mental regularities, is not entirely subject to the strict rules of necessity, but shelters also new elements. They are the basis for diversification and for providing the law of mind with an evolutionary trend. In the second and last chapter, we went through the three evolutionary modes tychasm, anancasm and agapasm which are characterized by the way chance and necessity are intertwined. Peirce rejects as theoretically inadequate both the theories that make chance the only positive agent of change (tychasm), as well as that attribute change to some necessary principle (anancasm). He makes agapic evolution, which sets love as the principle of attraction and harmonious inclusion of divergent strains in the unity of the cosmic continuum, in a way very similar in nature to that of the habit-taking process, to be the evolutionary principle of greater generality and intelligibility